MUTU DOLOK, RENDEMEN KAYU GERGAJIAN DAN KUALITAS PENGERJAAN KAYU AGATHIS (Agathis spec.) - Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Log's tapering of agathis (Agathis spec.), rangesfrom 0.5% to 5.5 % and tends to be morre silindical at 200 cm above the butt.The circularity of logs is more than 80 %, with the range of 81 % to 97 % at the butt and 83to 98 % at the top end.Recovery of wet sawn timber is 69,7 % on average. and ranges from 50 % to 82 %. The average specific gravity in air dried condition is 0.44 (= 440 kg/m3) with the range from 0, 42 to 0, 46 (420 kg/m3 to 460 kg/m3).Working properties of agathis wood is classified as easy; planing and moulding quality are classified as good to very good, while boring property is classified as medium.